Comparison of Strain Characteristics and Contact Resistances of Heavily Phosphorus‐Doped Si Formed by Phosphorus Implantation and In Situ Phosphorus‐Doped Si Epitaxial Growth. Issue 12 (29th March 2020) - Ko, Eunjung; Lee, Juhee; Shin, Hyunsu; Park, Seran; Ko, Daehong
Abstract : As transistor sizes reduce, the effect of contact resistivity on power consumption increases. To reduce contact resistivity, heavily phosphorus‐doped Si grown via in situ phosphorus‐doped (ISPD) Si epitaxial growth is studied actively. Laser spike annealing to the heavily phosphorus implanted (IMP) layers is demonstrated to replace ISPD Si epitaxial growth process and phosphorus profiles and strain characteristics are evaluated. Regardless of the doping method, the phosphorus concentrations of both samples and their tensile strains are equivalent. After laser annealing, the metal‐silicidation is conducted to measure contact resistivity. The Ni‐silicide formed on IMP sample has 3D clusters inducing greater morphological degradation than ISPD samples. The contact resistivity of IMP sample measured using the circular transmission line model (CTLM) (1.2–8.3 × 10 −8  Ω cm 2 ) is similar to that of the ISPD sample (1.1–5.5 × 10 −8  Ω cm 2 ) after Ni‐silicidation of the ISPD layer. This study performs strain engineering by achieving low contact resistance at lower cost while applying strain using the IMP process rather than the epitaxial process. Abstract : Comparison of the strain properties of phosphorus doped silicon formed by phosphorus implanted and in situ phosphorus‐doped. The same level of strain is applied regardless of the doping method. This implies that phosphorus acting as a stressor is present, suggesting that stress can also be applied through the phosphorus implantation with laser spike annealing treatment to suppress diffusion.